Aspectos etnobiológicos e etnoecológicos na pesca artesanal em três municípios do litoral sul do Espírito Santo - Oliveira, Ana Carolina Machado de (2018)
This study aims to relate the traditional knowledge of fishermen to the scientific literature, as regards ethnobiological and ethnoecological aspects of decapod crustaceans caught in artisanal fishing on the Southern coast of Espírito Santo. The research was done in Anchieta, Piúma and Marataízes cities, South coast of Espírito Santo, and data collection occurred between September 2016 and February 2017. The ethnografic method used consisted of: 1) participant observation method; 2) semi-structured interviews and questionnaires; 3) snowball method; 4) method of triangulation of results. A total of 92 artisanal fishermen were interviewed, all aged between 18 and 71 years. In Anchieta city the target species of the fishing are the sea-bob shrimp, pink shrimp and white shrimp, and in Piúma and Marataízes only the sea-bob shrimp. The carcinofauna, captured in the three municipalities, is composed mainly of crabs and swimming crabs. The fishermen demonstrated knowledge about the biology of the species of crustaceans captured, differentiating the juvenile stages of the adults, as well as an occurrence of sexual dimorphism, once they recognize the copulatory organ of male shrimps (petasma) and in the females the presence of a greenish color in the dorsal region characterized by ovary development. In crabs and swimming crabs, the respondents reported that the shape of the abdomen is different between the sexes. The habitat of decapod species has also been described. Fishermen considered crustaceans to be important for the environment because: 1) they play roles in the dynamics of the marine community, in the food chain and in the processes of organic matter cycling and energy flow; 2) are important for consumption; and 3) are used for bait and comercialization. When questioned about the fisheries closure season, fishermen consider important but incorrect for the region, which indicates the need of greater dialogue between enforcement agencies and fishing communities. The information of this research corroborates with the literatura and can function as a tool for the management of fishery resources, and on the decrease of the impact on the populations of the target species and fauna by-catch, aiming at the sustainability of fishing and the valuing of coastal communities of Southern Southern coast of Espírito Santo.